Interactive lecturing for meaningful learning in large groups - YEGEN, BERRAK; GÜLPINAR, MEHMET ALİ (TAYLOR & FRANCIS LTD, 2005)
In order to enhance the quality of integration of physiological basic concepts with clinical sciences and to facilitate problem solving skills, a 'structured integrated interactive' two-hour block lecture on growth hormone physiology was implemented. A template showing the central regulation of growth hormone release and its peripheral effects was developed as an advanced organizer. Based on this template, new information was presented. Student feedback demonstrated that the lecture, based on the expository teaching model and enhanced by different forms of question and problem solving activities, was successful and interactive. It was also more motivating and was able to keep the attention of the students in relatively higher levels throughout the lecture. Furthermore, students felt that they had made important gains in transferable problem solving skills and this opinion was supported by their performance in clinical cases. These findings reinforced the idea that systematic incorporation of active learning strategies into lectures may minimize many of the weaknesses of traditional lectures.
Keywords: MEDICAL-EDUCATION; SESSIONS; STRATEGY